Assembly of the cnidarian camera-type eye from vertebrate-like components - Kozmik, Zbynek; Ruzickova, Jana; Jonasova, Kristyna; Matsumoto, Yoshifumi; Vopalensky, Pavel; Kozmikova, Iryna; Strnad, Hynek; Kawamura, Shoji; Piatigorsky, Joram; Paces, Vaclav; Vlcek, Cestmir (Proceedings of the National Academy of Sciences of the United States of America, 2008)
Animal eyes are morphologically diverse. Their assembly, however, always relies on the same basic principle, i.e., photoreceptors located in the vicinity of dark shielding pigment. Cnidaria as the likely sister group to the Bilateria are the earliest branching phylum with a well developed visual system. Here, we show that camera-type eyes of the cubozoan jellyfish, Tripedalia cystophora, use genetic building blocks typical of vertebrate eyes, namely, a ciliary phototransduction cascade and melanogenic pathway. Our findings indicative of parallelism provide an insight into eye evolution. Combined, the available data favor the possibility that vertebrate and cubozoan eyes arose by independent recruitment of orthologous genes during evolution.
Keywords: Gene Expression Regulation; RNA, Messenger; Sequence Homology, Nucleic Acid; Rod Opsins; Cercopithecus aethiops; Eye; Vision, Ocular; molekulární sekvence - údaje; COS buňky; oční čočka; sekvenční homologie nukleových kyselin; Photoreceptor Cells, Invertebrate; Models, Biological; Chlorocebus aethiops; COS Cells; Lens, Crystalline; zrak; cilie; Pigmentation; Cubozoa; pigmentace; Animals; Vertebrates; Crystallins; biologické modely; oči; zvířata; regulace genové exprese; melaniny; Melanins; fotoreceptory bezobratlých; Microphthalmia-Associated Transcription Factor; Molecular Sequence Data; krystaliny; Cilia; transkripční faktor spojený s mikroftalmií; obratlovci; messenger RNA; tyčinkové opsiny